2011
DOI: 10.1016/j.actatropica.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Lutzomyia (Pintomyia) fischeri (Diptera: Psychodidae: Phlebotominae), a probable vector of American Cutaneous Leishmaniasis: Detection of natural infection by Leishmania (Viannia) DNA in specimens from the municipality of Porto Alegre (RS), Brazil, using multiplex PCR assay

Abstract: In order to determine natural Leishmania (Viannia) infection in Lutzomyia (Pintomyia) fischeri, a multiplex PCR methodology coupled to non-isotopic hybridization was adopted for the analysis of sand fly samples collected by CDC light traps in an endemic area of American Cutaneous Leishmaniasis (ACL) in the periurban region of the municipality of Porto Alegre, Rio Grande do Sul State, Brazil. We analyzed by PCR methodology 560 specimens of Lutzomyia (Pintomyia) fischeri (520 females and 40 males). The wild sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
1
24
0
5
Order By: Relevance
“…Some studies have discussed the potential role of L. (P.) fischeri in maintaining the wild enzootic disease, in association with L. (V.) braziliensis (rangel & lainson 2009;Pita-Pereira et al 2011). In the present study, it was observed that the species did not occur continuously over the trapping period, and that separate peaks above X W occurred independently of whether the months were cold or hot.…”
Section: E-issn 1983-0572mentioning
confidence: 56%
See 1 more Smart Citation
“…Some studies have discussed the potential role of L. (P.) fischeri in maintaining the wild enzootic disease, in association with L. (V.) braziliensis (rangel & lainson 2009;Pita-Pereira et al 2011). In the present study, it was observed that the species did not occur continuously over the trapping period, and that separate peaks above X W occurred independently of whether the months were cold or hot.…”
Section: E-issn 1983-0572mentioning
confidence: 56%
“…On the other hand, L. migonei (França) probably acts as a secondary vector in this state (Pita-Pereira et al 2005;rangel & lainson 2009). Pita-Pereira et al (2011) determined natural Leishmania (Viannia) braziliensis (Vianna) infection in Lutzomyia (Pintomyia) fischeri (Pinto), using multiplex PCR methodology in an endemic area of American Cutaneous Leishmaniasis (ACL) in the periurban region of the municipality of Porto Alegre, Rio Grande do Sul State, Brazil. The present study had the objective of generating qualitative and quantitative data on the leishmaniasis vectors that frequent peridomestic environments, thus contributing towards adding information on the process of disease transmission in this state.…”
Section: _____________________________________mentioning
confidence: 99%
“…For two other species of Phlebotominae recorded in this study, L. h. hirsuta and L. fi scheri, although they are associated with ACL transmission cycles in other Brazilian states (the latter recorded with natural infection by L. (V.) braziliensis) (24) , the current data do not show epidemiological signifi cance for either in the CFMA (1) .…”
Section: Statistical Analysis Of the Collected Datamentioning
confidence: 38%
“…43,44 Knowledge of the peridomiciliary breeding sites of phlebotomine sand flies could help orient environmental intervention measures that would impede the breeding of these insects and justify the application of insecticides to control household transmission. 45 It was found that reorganizing and cleaning of the peridomicile and the application of residual insecticides in houses and outbuildings significantly reduces sand fly populations in ACL-endemic areas modified by human activities.…”
Section: Weeks)mentioning
confidence: 99%